Stock price related financial fragility and growth patterns - Pascal Aßmuth (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
The total output of an economy usually follows cyclical movements which are accompanied by similar movements in stock prices. The common explanation relies on the demand side. It points out that stock market wealth drives consumption which triggers production afterwards. This paper focuses on influences via the supply side of the economy. The aim of the paper is to explore channels where stock price patterns influence the amount of credit taken by firms. The author examines trend and volatility cycles on the stock market. There are three channels addressed: the stock market valuation as piece of information for the assessment of a firm's creditworthiness, the influence on restructuring prospects in times of financial distress and the stock market related remuneration of the top management affecting capital demand. The author ask to which extent a channel may contribute to the stock price - output relation when there is mutual feedback. A model à la Delli Gatti et al. (A new approach to business fluctuations: heterogeneous interacting agents, scaling laws and financial fragility, 2005) drives the results. Firms take credit to finance their production which determines their financial fragility. If their stochastic revenue is too low, they are bankrupt and leave the economy. The capital loss hurts the bank's equity base and future credit supply is diminished. This causes business cycles. Results show that if the bank assesses creditworthiness according to the stock price then idiosyncratic stock price fluctuations have only a slight effect as they disturb selection and hinder growth. If stock market optimism matters for bankruptcy ruling the level of stock owners' influence does not matter. If optimism is wide spread among stock investors however, investment behaviour is also correlated through the stock prices and this results in huge real economy cycles without any long-term growth. If volatility is considered in the decision of managers they act more prudently and this fosters growth.
Keywords: E32; G30; C63; 330; Heterogeneous agents models; financial fragility; stock prices; business cycles